Implementasi Program Pengembangan dan Pemberdayaan Masyarakat (PPM) Berbasis Kearifan Lokal PT. CLM dalam Meningkatkan Kemandirian Ekonomi Masyarakat di Kabupaten Luwu Timur - Fauziyyah B; Nurlaelah Abbas; Mustari Mustafa; Asni Djamereng (Universitas Islam Negeri Alauddin Makassar, 2025)
The main issue of this study is how the implementation of PT CLM's community development and empowerment program (PPM) based on local wisdom can improve community independence in East Luwu Regency. This study has two research questions: 1) How does local wisdom support the success of the PPM program implemented by PT CLM in East Luwu Regency? 2) What are PT CLM's strategies for implementing local wisdom to increase economic independence through the PPM program in East Luwu Regency? This study uses descriptive qualitative research with a community empowerment approach, which emphasizes active community participation and the utilization of local potential as the foundation for economic development. Data were obtained through observation, interviews, and documentation techniques, with data sources including PT CLM PPM managers, Rumah Coklat managers, and Laskap Village officials. The results of this study indicate that the Community Development and Empowerment (PPM) program, particularly Rumah Coklat, is able to utilize local wisdom in the form of cocoa farming traditions, mutual cooperation values, and the community's generational knowledge of cocoa management. The integration of these local potentials encourages an increase in product added value, opens up business opportunities, and strengthens the community's capacity to manage businesses independently. The strategies implemented by PT CLM include training, technical assistance, provision of processing facilities, and continuous collaboration with the local community. The conclusion of this study confirms that the implementation of PPM based on local wisdom by PT CLM has contributed positively to improving the economic independence of the Laskap Village community through strengthening production capacity, increasing knowledge, and developing cocoa-based businesses. The implications of this research indicate that the development of community empowerment programs based on local wisdom can be a model for sustainable empowerment, strengthening community economic resilience, and emphasizing the importance of collaboration between companies, communities, and governments in development practices based on local potential.